PENINGKATAN PENGETAHUAN DIET NUTRISI DAN CAIRAN PADA KELUARGA PENDERITA GAGAL GINJAL KRONIK DALAM PERAWATAN HEMODIALISA MELALUI EDUKASI KESEHATAN - Wahyuni, Emmi; Rahmawati, Lutfiasih; Hidhayanti, Hayyu Naafi; Dewi, Nurhayati Veryanti; Mayasari, Dian (LPPM Universitas Flores, 2024)
Chronic kidney disease is a global health problem that affects millions of people worldwide. Chronic renal failure as the final stage of kidney disease, requires comprehensive management, starting from regular hemodialysis to self-care management of the patient at home. Fluid and nutritional management is an important aspect that patients and families must pay attention to. Lack of availability and effectiveness of nutrition and fluid education programs specifically aimed at patient families. Many families of chronic kidney failure patients experience difficulty in adapting and implementing appropriate nutritional recommendations in daily life. This community service aims to provide comprehensive education, which provides relevant and up-to-date information about nutrition and fluids and involves families in an interactive learning process. Community service activities were carried out using direct health education methods for 16 families of patients undergoing hemodialysis. The evaluation method is carried out by filling out a pre-and post-test design knowledge questionnaire. The activity was carried out on May 17 2024 in the hemodialysis treatment room at Hermina Daan Mogot Hospital. The results of community service activities show an increase in knowledge regarding nutritional diet and fluids in the families of patients undergoing hemodialysis. It is hoped that the community service team nurses will then directly assist families regarding nutritional diet and fluids for patients undergoing hemodialysis and then monitor its long-term implementation at home either online or offline.